Micro-engineered lung-on-a-chip system to study nanotoxicity - Teo, Yu Rong (2019)
Microfluidics, as its name suggests, involves the use of devices with micro-sized channels for analysis and control of minute volumes of fluid. Originated in the 1990s, it has since become predominant in a wide variety of applications, ranging from research to commercial biotechnologies. One such application is a lab-on-a-chip whereby a replicated laboratory environment is integrated onto a single chip platform, allowing for high throughput, ease of analysis. Typically, traditional photolithography techniques are used for fabrication of these devices. However, alternative methods such as 3D printing have been explored to exploit their unique advantages, and to verify and substantiate their feasibility in such applications. Similarly, nanoparticles have also garnered interest in a wide variety of applications, mainly due to their large surface area compared to bulk materials, making them highly versatile. Prior to the implementation of nanoparticles in large-scale applications, it is crucial to investigate the effects of nanotoxicity that these particles have on human lung cells and their potential health hazards induced when inhaled or subjected to long-term exposure. The study aims to analyse the effects of nanotoxicity of nanoparticles on a lung-on-a-chip model and evaluate the feasibility of 3D printed moulds for fabrication of microfluidic devices as compared to those produced by photolithography methods. The various findings and observations will be presented in this report.